Osebne zgodbe o življenju v Egiptu in doma - Koprivec, Daša (Etnolog. Nova vrsta (Ljubljana), 2016)
The article presents personal stories of aleksandrinke and their children about life in Egypt and at home. The reasons why the aleksandrinke went to Egypt were very different and ranged from economic to emotional ones. Living in Cairo or Alexandria as wet nurses, nannies, chambermaids, or companions they acquired a variety of skills, from learning foreign languages to child education. This broadened their horizon considerably and those who returned home after many years of living in Egypt found it hard to re-adapt to the domestic environment. Some aleksandrinke were joined in Egypt by their children, less often their husbands. When they married in Egypt, it was mostly to a non-Slovene. Many children of the aleksandrinke emigrated to Australia or Canada in the 1950s.
Keywords: aleksandrinke; Slovenes; Slovenke; slovenske izseljenke; Egipt; Egypt; ljudsko življenje; življenjske zgodbe